Identificación de compuestos bioactivos y actividad antienzimática del extracto etanólico de hojas de Hesperomeles cuneata Lindl. - Fernández-Rebaza, Gustavo Adolfo (2025)
Introduction. Research on medicinal plants has allowed the development of new treatment alternatives. Hesperomeles cuneata Lindl. is a species for which few scientific studies are available; however, its anti-enzymatic activity has not been reported. Objectives. To identify the bioactive compounds and evaluate the anti-enzymatic activity of the ethanolic extract of leaves of Hesperomeles cuneata Lindl.  Methods. An experimental study was carried out where leaves of Hesperomeles cuneata Lindl. were collected in Santiago de Chuco, La Libertad. The plant material was dried and pulverized, then it was subjected to a maceration process with ethanol to obtain the extract. The solubility of the extract was evaluated with different solvents, and the identification of bioactive compounds was executed by phytochemical screening and thin layer chromatography (TLC). The anti-enzymatic activity of the extract was evaluated by in vitro assays, in which its inhibitory capacity on elastase and collagenase enzymes was determined, using a positive control of epigallocatechin gallate (EGCG). Results. The ethanolic extract presented high solubility in methanol and ethanol. Phenolic compounds, flavonoids, tannins, alkaloids, lactones, among others were identified. Anti-elastase activity was determined with an IC₅₀ value of 73,889 µg/mL and anti-collagenase activity with an IC₅₀ of 76,4814 µg/mL, evidencing its significant inhibitory capacity of the extract on both enzymes. Conclusion. The ethanolic extract of Hesperomeles cuneata Lindl. leaves evidenced bioactive compounds such as flavonoids, phenolic compounds, lactones, tannins, among others, and presented inhibitory activity on elastase and collagenase enzymes.